PENGENDALIAN KUALITAS PADA PROSES LOOM DENGAN MENGGUNAKAN METODE SIX SIGMA (Science and Technology (SciTech), 2023)
Developments in the industrial sector are currently growing rapidly so that the company is committed to producing high quality products. PT. Dasaplast Nusantara is a company engaged in the plastics industry in Pecangaan District, Jepara Regency. Producing products (PP Woven Bag, &InnerBag, Leno Mesh Bag, and Warring Agronet) according to customer standards, with a make to order production system applied. The purpose of this research is to find out the causes of rejects produced by looms and determine the improvements that must be made to minimize the occurrence of product rejects using the DMAIC method on six sigma. Using the Six Sigma Method, it will be known how many levels of defects and influences or problems that occur in the Loom production process. Can use Control Chart P, Pareto Diagram and Fishbone. The most common cause of defects is labor that is less thorough because many orders are made and because the machines used are not performing well. From the results of the calculation of observations from January to December 2022, the DPMO value was 132,364 m from a million sack production and was at the 2.62 sigma level. In the observations from January to March 2023, a DPMO value of 2173 was obtained from a million sack products and was at a level of 4.36.